(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2023)
This work addresses the concept of information regime, analyzing the segment "AL TV nas Comunidades", from TV Gazeta de Alagoas, which exposes the problems of local communities to the public power. The general objective is to examine the journalistic information production regime, verifying its effectiveness. The adopted methodology combines the Immanent Study Method with a qualitative and quantitative approach. Field research involves journalists, residents, directors, politicians and sponsors. Data analysis identifies positive and negative points of the situation, proposing improvements. The inferences are based on the adopted theoretical framework, contributing to the understanding of the informative process in journalistic production.